Indonesia Multy sector collaboration dalam Pengembangan UMKM Di Kabupaten Malang - Fajrin Maulana; Muhammad Shaddam R. M; Muhammad Kamil (Bahasa Indonesia, 2021)
UMKM development multi sector collaboration, namely the development of UMKM that work together in various fields or sectors to overcome problems faced or to achieve common goals. The government can develop UMKM cooperation in various fields (multi-sector collaboration) to achieve the specified goals, or to improve the economy of Malang district. Multi sector collaboration is very important to do, because with collaboration/cooperation, the possibility of the success of a business that will be or is being run will increase more rapidly than being run alone. The type of research used is descriptive with a qualitative approach. Data was collected using observation and interview techniques. The data analysis technique is using data reduction, data presentation, and conclusion. Based on the results of this study, the Government through various sectors such as the Ministry of Cooperatives, the Ministry of Industry and Trade, Bappenas, State-Owned Enterprises, as well as banks and non-bank financial institutions, the government has made various efforts to realize the development of small, medium and micro enterprises. In this case, good cooperation between the government and the SME sector in the empowerment process is very necessary, so that the empowerment program is not one-sided.